OCT angiography and Color Doppler Imaging in the study of hemoperfusion in the retina and optic nerve in POAG - N. I. Kurysheva; E. V. Maslova; A. V. Trubilina; A. V. Fomin (Oftalʹmologiâ, 2016)
Purpose: To evaluate the hemoperfusion of Optic Nerve Disk (OND), peripapillary and macular areas, and retrobulbar blood flow in patients with primary open-angle glaucoma using optical coherence tomography with angiography (OCT-A) and Сolor Doppler Imaging (CDI).Patients and Methods: 65 eyes of patients with primary open angle glaucoma (POAG) and 22 eyes of age-matched healthy subjects were examined using the SD-OCT-А (RtVue xR Avanti with the AngioVue software). Retinal Thickness and Angio Flow Density (AFD) were measured. AFD Disc and Peripapillary Flow Density were measured in OND and in peripapillary area. AFD Retina were evaluated in Macula inсluding Fovea- and Parafovea regions (superficial and deep) of the inner retinal layers. Ophthalmic Artery (OA), Central Retinal Artery (CRA), Posterior short Ciliary Arteries (PCA), Central Retinal Vein (CRV) and Vortex Vein (VV) were measured by CDI. Statistical analysis was performed using SPSS version 21 and MASS library of language R. The value of each diagnostic indicator (z-value) was calculated with the Wilcoxon-Mann-Whitney test and the area under the receiver operating characteristic curve (AUC).Results: Both OCT-A and CDI indicators were reduced in glaucoma compared to healthy eyes. The following indicators had the largest AUC and diagnostic value (z-value) to discriminate the early glaucoma from normal eyes: AFD Retina Superficial Whole En Face (z = 3,83, p<0,0001; AUC 0,8 (0,69‑0,90), AFD Retina Deep Whole En Face (z = 3,31, p = 0,0007; AUC 0,76 (0,64‑0,88), Peripapillary Vessel Density (z = 3,2, p = 0,001; AUC 0,75 (0,63‑0,87), end-diastolic flow velocity in AO (z = 3,03, p = 0,002; AUC 0,74 (0,61‑0,86) and in TPCA (z = 2,78, p = 0,005; AUC 0,72 (0,58‑0,86); and to discriminate the early glaucoma from the advanced and far advanced stages: AFD Disc Peripapillary Inferior Temporalis (z = 5,61, p<0,0001; AUC 0,94 (0,86‑1,0) and the mean flow velocity in the CRA (z = 4,16, p<0.0001; AUC 0,81 (0,69‑0,92).Conclusion: The results revealed a deficit of hemoperfusion in ONH and peripapillary and macular areas measured by OCT-A in glaucoma. CDI provides the additional information of a blood flow in the eye leading for better understanding of glaucoma pathogenesis. The both methods complement each other in early glaucoma detection and monitoring.